Relações entre tamanho populacional, uso do habitat, dieta e predação de ninhos por Nasua nasua (Carnivora, Procyonidae) em remanescentes florestais - Ruim, Juliana Bombarda [UNESP] (2014)
The forest fragmentation creates mosaics of reduced and discontinuous natural habitats patches, inserted, sometimes, in inhospitable matrix. Many mammals, like large carnivores, are not able to keep their populations in small remnants, whereas others, as mesopredators, may thrive in these areas, showing overabundant populations. The coatis, Nasua narica e N. nasua, are some of species that may remain in areas substantially modified and that, in high densities, exert strong pressure on the resources consumed by them, affecting, among others, the crops around the fragments and the avifauna by preying on nests. Coatis occupy more frequently forested habitats due to, besides others reasons, the higher food availability usually provided by them. Nevertheless, agricultural matrices are commonly used as a habitat and the crops surrounding the fragments may be important items in the diet of these animals. Thus, the aim of the present work was to examine and to compare population density, habitat use, diet and the predation on ground nesting birds by Nasua nasua and some others mesopredators in two forest fragments of different sizes. The study was carried out in fragments of semideciduous forest, one of them with 680 hectares and the other with 354 hectares. The density data were collected through population census by line transects and were analyzed by the Distance program; the habitat use was recorded by walking on existent trails, observing the animals, and by the distribution of fecal samples at old-growth forest, second-growth forest and edge; the diet was verified through fecal samples and direct observations of the foraging individuals; the nest predation was studied using an experiment with artificial nests. The population density was higher in the smaller fragment as was the nest predation rate, and these seem to be related to the diminished size and isolation of the area, which make the permanence of the natural predators and the ...